ANALISIS GAYA BAHASA PADA AKUN INSTAGRAM @KUMPULAN_PUISI DAN IMPIKASINYA TERHADAP PEMBACA - Eponiah Eponiah; Irfan Juhairi (Universitas Maritim AMNI Semarang, 2022)
The purpose of this study is to understand the style of language used in postings on the Instagram account @kumpulan _puisi and its implications for literary connoisseurs on Instagram social media. . The method used in this research is a descriptive quantitative method. The source of the data that the author obtained is from posts contained in the @kumpulan_puisi account on Instagram social media and the accompanying comments. The data collection technique that the author uses is by reading deep understanding and appreciation and meaning. The data analyzed is the use of the language style used and its implications in the comments column by the readers, where the readers participate in replying to posts with poetry in a language style that is in accordance with contained in the post. Lexically, the poetry language style used in the @kumpulan _puisi real account emphasizes its meaning, and forms a rhetorical statement that involves the reader in understanding the meaning of the poem.